Conversion of hemicellulose using acidic ionic liquids - Dhepe, Paresh Laxmikant; Matsagar, Babasaheb Mansub (WO2015111086 A1, 2014)
The present invention discloses one pot process for the conversion of hemicellulose into C5 sugars using ionic liquids in water media.